Neutrosophic Digraph with Generalized Modus Tollens - Elsayed Badr, Shokry Nada, Ashraf ELrokh, Hoda Mostafa (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
In this paper, we generalize modus tollens method for neutrosophic digraph by using neutrosophic rule and define degree of a vertex in neutrosophic digraph, Indegree of a vertex in neutrosophic digraph, out degree of a vertex in neutrosophic digraph and generalized modus tollens are discussed.